Removal of bacterial pathogen from wastewater using Al filter with Ag-containing nanocomposite film by in situ dispersion involving polyol process - Seo, Young Ik; Hong, Ki Ho; Kim, Se Hoon; Chang, Duk; Lee, Kyu Hwan; Kim, Young Do (ELSEVIER SCIENCE BV, 2012)
In this study, a filter with deposited Ag/Al(OH)(3) mesoporous nanocomposite film was fabricated to remove bacterial pathogens from wastewater. Mesoporous Al(OH)(3) film was generated on the Al foam body by alkali surface modification, followed by immersion in a polyol solution for 4 h at an elevated temperature in order to deposit silver nanoparticles (Ag NPs). The Al(OH)(3) porous matrix showed a significant increase in specific surface area due to the large size of the voids between flakes, which reached several tens of nanometers. After in situ three-dimensional deposition of Ag NPs by a polyol process, the Ag NPs were nucleated and grown at the surface of the mesoporous Al(OH)(3) film. The filter with Ag/Al(OH)(3) mesoporous nanocomposite film showed a good bacterial pathogen removal rate within a very short contact time compared to the untreated Al foam filter. Filters with deposited Ag/Al(OH)(3) mesoporous nanocomposite film have great potential for application as antimicrobial filters for tap water purification, wastewater treatment, and other bio-related applications. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: SILICA THIN-FILMS; SILVER NANOPARTICLES; ESCHERICHIA-COLI; IONS; DISINFECTION; RESISTANCE; TOXICITY; NITRATE; AGENT